INFLUENCE OF ABUSIVE SUPERVISION ON EMPLOYEES’ MORALE AT WORK: EVIDENCE FROM THE MANUFACTURING ORGANISATIONS IN NIGERIA - Oginni, Babalola (Annals of Spiru Haret University. Economic Series, 2024)
Organization is structured in such a way that people work together wherein some would be superiors and others would be subordinates which makes supervision a natural phenomenon while the quality of supervision will determine the result of operational activities daily. The study focused on the influence of abusive supervision on employee morale using the manufacturing sector as the unit of analysis, it identified the level of abusive supervision, the causes of abusive supervision, and the relationship between abusive supervision and employee morale. Yamane’s sample size formula was used to get the sample size of 310 while a multistage sampling technique was used to select the sample and administer the questionnaire. it was found that abusive supervision is high, caused by leadership styles, absence of an alternative job, and family demands and there exists an inverse relationship between abusive supervision, and employee morale with implications on employee and behavioural outcomes, and concluded that high abusive supervision heralds low job satisfaction, low commitment, and low loyalty thus, leading to decreased productivity, increased grievances, and increased turnover as well as hindering innovation and collaboration. Training was recommended to focus on supervision with empathy to improve interpersonal relationships and feelings of belongingness.